The Math+ protocol in Covid-19 - Joseph Varon (World Nutrition Journal, 2022)
COVID19 is a highly heterogeneous and complex medical disorder; indeed, severe COVID-19 is probably amongst the most complex of medical conditions known to medical science. While there is no single ‘Silver Bullet’ to cure COVID-19, this severely disturbed pathological processes leading to respiratory failure in patients with COVID-19 organizing pneumonia will respond to the combination of Methylprednisone, Ascorbic acid, Thiamine, and full anticoagulation with Heparin (MATH+ protocol).